Growing city farming together: A 5-year Bay Area urban agriculture & food systems needs assessment with models, barriers and recommendations to shape community engaged programming - Rob Bennaton; Julio Contreras; Yulia Baltusova Lamoureaux (Urban Food Systems Symposium, 2022)
Urban agriculture and food systems in the California Bay Area are multifaceted and intricate. There are many successful models and inspirational stories of coalition building, thousands of pounds of local food production, and overall community empowerment. Our presentation will highlight case examples, challenges, barriers, and recommendations in the University of California Cooperative Extension’s (UCCE) Urban Ag & Food Systems Program’s (UAFSP) 2019 Bay Area Needs Assessment. The needs assessment summarizes and discusses research, outreach projects and extension services the UAFSP conducted during the years 2014-2019 in five Bay Area Counties. It comprises both quantitative and qualitative information gathered from soil analysis, research, participatory research, workshop surveys, site visits and technical extension services. Projects include grant projects like USDA Beginning Farmer & Rancher Development Program workshops across California. Also, the program conducted an urban farmer’s mini-grant program with the Alameda County Resources Conservation District designed with low entry and an easy application process. The UAFSP’s projects provide a unique snapshot of urban food production systems and challenges growing in urban environments in disenfranchised communities experiencing higher levels of food insecurity and environmental injustice. One of the assessment's conclusions was that land access, technical education and economic viability remain the highest challenges faced by urban agriculture and food systems groups. Most groups thrived on the social, cultural and services aspects of producing local affordable food, transforming lives, and serving important roles in their communities as food hubs, green spaces, and empowering sites. But these accomplishments were difficult to achieve due to the economic and political aspects that create an eb and flow of activity depending on grants, available resources, community, and political stakeholders. A suggested framework for supporting local food production and enhancing local food systems that presents itself is to support urban residents in becoming community food producers (AB 1990), who can not only grow local food but also safely and legally prepare and package value added products through CA Cottage Food Act (AB 1616); in the process boosting the local economy and food system by becoming a micro enterprise home kitchen operation (AB 626).